Effects of applying glutaraldehyde-containing desensitizer formulations on reducing dentin permeability - Hiroshi Ishihata; Masafumi Kanehira; Werner J. Finger; Hidetoshi Shimauchi; Masashi Komatsu (Elsevier, 2012)
Background/purpose: The efficacy of dentin-desensitizing agents is commonly evaluated in clinical studies by measuring patients' pain response upon stimulation. Although indispensable, such trials are time-consuming, and the results depend on an individual's subjective pain rating. Therefore, in vitro efficacy screening prior to clinical testing is highly desirable. The objective of this study was to investigate in vitro dentin permeability of two glutaraldehyde-containing desensitizer formulations after different modes and times of application. Materials and methods: Coronal tooth slices, 1.3 mm thick, were dissected from 60 freshly extracted third molars. Specimens were treated with EDTA to remove the cutting smear. The dentin disks were clamped in a split chamber device to determine the baseline permeability under a liquid pressure of 2.5 kPa for 2 minutes and 13 kPa for 1 minute, to record liquid flow through the dentin using a photochemical method. Slices were soaked in a 2% albumin solution and reevaluated under the same pressure cycles prior to active or passive application for 15, 30, or 60 seconds of either Gluma Desensitizer or Gluma PowerGel (GDP) (Heraeus Kulzer, Hanau, Germany) and then reevaluated. Dentin-disk permeability was determined as the area under the photo signal output voltage line during the pressurizing period (mV s). The statistical data analysis used a Kruskal-Wallis ANOVA and Mann-Whitney post-hoc test with the significance level set to 5%. Results: Permeability at the baseline and after albumin soaking did not significantly differ. For both desensitizing compounds, 30 and 60 seconds of active and passive applications resulted in significantly reduced dentin permeability. After the 15 second application, only the actively treated samples with GDP showed a significant reduction in permeability. Conclusions: The liquid and the gel desensitizing agents both significantly reduced dentin permeability. The obvious advantage of a gel formulation is the controlled application, limited to the hypersensitive tooth area, thus avoiding inadvertent contact with adjacent gingival tissues.